The craft of political research - Shively, W. Phillips 1942- (New York, NY Routledge,Taylor & Francis Group, 2017)
The Craft of Political Research immerses readers not only in how political scientists work but also in how ideas produce research questions and guide the selection of research methods. Emphasizing the internal logic of research methods and the collaborative nature of the research process, this slender text explores the design behind interesting questions, problems in measurement and analysis, and key statistical methods. The Craft of Political Research's elegant explanations inspire a big picture understanding of how political scientists explain political reality and encourage students to create their own inventive, original, and bold research work.
Doing research -- Political theories and research topics -- Importance of dimensional thinking -- Problems of measurement: accuracy -- Problems of measurement: precision -- Causal thinking and design of research -- Selection of observations for study -- Introduction to statistics: measuring relationships for interval data -- Introduction to statistics: further topics on measurement of relationships -- Introduction to statistics: inference, or how to gamble on your research.
Includes bibliographical references and index.
Keywords: Political science -- Research -- Methodology